2020
DOI: 10.21873/cgp.20231
|View full text |Cite
|
Sign up to set email alerts
|

lincRNA-RP11400K9.4 Regulates Cell Survival and Migration of Breast Cancer Cells

Abstract: Background/Aim: Several works in the past decades pointed out the key role of long intergenic non-coding RNA (lincRNA) in breast cancer development. Here in we report for first time the importance of deregulation of lincRNA RP11-400K9.4 in breast cancer cells which played a role in cell survival and migration. Materials and Methods: After RP11-400K9.4 silencing by short hairpin RNAs or overexpression by GeneBlocks, real-time quantitative polymerase chain reaction (RT-PCR), microarray, migration, proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Long noncoding RNAs (lncRNAs) are a series of transcripts longer than 200 nucleotides that have limited protein coding capability [3][4][5]. Several studies have reported that the deregulation of lncR-NAs, such as LncRNA RP11-400K9.4 [6], lncRNA DILA1 [7], and LncRNA OIP5-AS1 [8] affects the tumorigenesis and progression of breast invasive carcinoma (BRCA). However, the detailed mechanism underlying the regulation and alteration of these lncRNAs in BRCA over time remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are a series of transcripts longer than 200 nucleotides that have limited protein coding capability [3][4][5]. Several studies have reported that the deregulation of lncR-NAs, such as LncRNA RP11-400K9.4 [6], lncRNA DILA1 [7], and LncRNA OIP5-AS1 [8] affects the tumorigenesis and progression of breast invasive carcinoma (BRCA). However, the detailed mechanism underlying the regulation and alteration of these lncRNAs in BRCA over time remains unknown.…”
Section: Introductionmentioning
confidence: 99%